2021
DOI: 10.1007/s10591-021-09567-9
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and Self Differentiation: The Role of Fear of Intimacy and Insecure Adult Attachment

Abstract: It is suggested in literature that there is a link between Alexithymia and Self-Differentiation; however, little is known about possible mediation factors. The goal of this work is to test in a non-clinical population of adults the mediation role of Fear of Intimacy and Adult Attachment in the relationship between Alexithymia and Self-Differentiation. A sample of 258 participants self identified as gay or lesbian, aged 20–50 years (M: 30.29; SD: 7.27), 45% of whom were males, completed self-reported measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Findings from the present study revealed that AEE could also influence subjective wellbeing through serial mediation by fear of intimacy and attachment avoidance. Previous research has demonstrated that fear of intimacy is related to attachment difficulties ( 72 ). Based on the interpersonal model of intimacy ( 73 ), a romantic relationship that involves self-disclosure and responsiveness may feel rewarding.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from the present study revealed that AEE could also influence subjective wellbeing through serial mediation by fear of intimacy and attachment avoidance. Previous research has demonstrated that fear of intimacy is related to attachment difficulties ( 72 ). Based on the interpersonal model of intimacy ( 73 ), a romantic relationship that involves self-disclosure and responsiveness may feel rewarding.…”
Section: Discussionmentioning
confidence: 99%
“…This process does not occur in isolation, but rather in the context of close and enduring relationships with others. Consequently, adolescents with alexithymia are at a higher risk of developing insecure attachment styles ( Besharat et al, 2014 ; Scigala et al, 2021 ). According to I-PACE, disordered characteristics of persons tend to shape associated affective and addictive behavioral responses.…”
Section: Introductionmentioning
confidence: 99%
“… Thorberg and Lyvers (2010) showed that self-differentiation is strongly associated with attachment. Another study showed that adult attachment acts as a mediator between self-differentiation and Alexithymia ( Scigala et al., 2021 ). Wilson (2021) investigated the mediating role of differentiation of self and the results indicated that high levels of relationship satisfaction associated powerfully with differentiation of self, and couples who had high differentiation of self increase their relationship satisfaction more than others ( Neophytou et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%